PIV investigation on corner separation control in a compressor cascade based on a vortex generator - Sun, Shuxian; Zhou, Ling; Zhu, Yichen; Zhu, Huiling; Meng, Tongtong; Ji, Lucheng (Journal of visualization, 2024)
To deepen the understanding of flow mechanisms related to corner separation and associated control techniques, a passive control scheme based on a vortex generator (VG) installed on the end wall of the cascade passage was adopted. Detailed particle image velocimetry investigations were performed at different attack angles and flow velocities in a low-speed wind tunnel. At a 5° attack angle, the VG control cascade can effectively suppress the corner separation for chord Reynolds numbers (Re c ) of 2.1 × 10 4 and 3.1 × 10 4 . As Re c increases to 3.8 × 10 4 and 4.8 × 10 4 , the original separation zone is relatively small, and the strong trailing vortex generated by the VG fails to intersect it, instead producing excessive interference to the main flow, resulting in additional flow loss. The separation zone is generally small at a 0° attack angle, and the VG control cascade performs similarly to that at the 5° attack angle . Through analysis of the instantaneous velocity and vorticity, it is discovered that the primary mechanism by which the VG suppresses corner separation is the unsteady disturbance of the trailing vortex to the separation, which increases the kinetic energy in the separation zone, lowers the accumulation of low-energy fluid, thereby suppressing the corner separation. Graphic Abstract